ИЗУЧЕНИЕ АНТИБАКТЕРИЦИДНЫХ И АНТИФУНГИЦИДНЫХ СВОЙСТВ АЦЕНТОНОВЫХ И СПИРТОВЫХ ЭКСТРАКТОВ ПЛОДОВЫХ ТЕЛ HERICIUM ERINACEUS - Киреенко, Н А; Макарчикова, Ю Ю; Дегтярёва, Елена Ивановна; Атанасова, Юлия Васильевна (FORCIPE, 2021)